Culture against man - Jules, Henry (New York, 1963)
THIS BOOK IS ABOUT CONTEMPORARY AMERICAN CULTURE -its economic structure and values, and the relation of these to national character, parent-child relations, teenage problems and concerns, the schools, and to emotional breakdown, old age, and war. This is not an objective description of America, but rather a passionate ethnography; the emphasis is on description and interpretation rather than on program for change. Though in parts of this book I suggest ways of changing conditions I de plore, in much of it I do not, because over the six years spent in writing I have not been able to perceive immediate possi bilities for change. For example, though I deplore the fact that the elementary school pitches motivation at an intensely com petitive level, I see no sense in altering that approach, because children have to live in a competitive world. Thus though I often describe rather grim situations, I try also to be aware of the complex interrelationships in culture and of the fact that even though one may regret what one describes, usually he cannot make practicable suggestions for change.
Keywords: Sociology 2. Social condition